if p=2-√5/2+√5 and q=2+√5/2-√5 find the value of p + q
Answers
Answered by
37
______________________________
= ( 2 – √5 ) / ( 2 + √5 ) × ( 2 – √5 ) / ( 2 – √5 )
= ( 2 – √5 )² / ( 2² – √5² )
= ( 4 – 4√5 + 5 ) / ( 4 – 5 )
= 9 – 4√5
______________________________
= ( 2 + √5 ) / ( 2 – √5 ) × ( 2 + √5 ) / ( 2 + √5 )
= ( 2 + √5 )² / ( 2² – √5² )
= ( 4 + 4√5 + 5 ) / ( 2 – 5 )
= 9 + 4√5
______________________________
Now, putting the values of p and q in the given equation :-
= 9 – 4√5 + 9 + 4√5
= 18
______________________________
Answered by
57
Given That
p=(2-√5)/(2+√5)
And q=(2+√5)/(2-√5)
Then We Find The Value Of p+q
![p + q = \frac{2 - \sqrt{5} }{2 + \sqrt{5} } + \frac{2 + \sqrt{5} }{2 - \sqrt{5} } p + q = \frac{2 - \sqrt{5} }{2 + \sqrt{5} } + \frac{2 + \sqrt{5} }{2 - \sqrt{5} }](https://tex.z-dn.net/?f=p+%2B+q+%3D++%5Cfrac%7B2+-++%5Csqrt%7B5%7D+%7D%7B2+%2B++%5Csqrt%7B5%7D+%7D++%2B++%5Cfrac%7B2+%2B++%5Csqrt%7B5%7D+%7D%7B2+-++%5Csqrt%7B5%7D+%7D+)
![p + q = ( \frac{(2 - \sqrt{5})(2 - \sqrt{5}) + (2 + \sqrt{5} )(2 + \sqrt{5} ) }{(2 + \sqrt{5})(2 - \sqrt{5}) } ) p + q = ( \frac{(2 - \sqrt{5})(2 - \sqrt{5}) + (2 + \sqrt{5} )(2 + \sqrt{5} ) }{(2 + \sqrt{5})(2 - \sqrt{5}) } )](https://tex.z-dn.net/?f=p+%2B+q+%3D+%28+%5Cfrac%7B%282+-++%5Csqrt%7B5%7D%29%282+-++%5Csqrt%7B5%7D%29+%2B+%282+%2B++%5Csqrt%7B5%7D+%29%282+%2B++%5Csqrt%7B5%7D+%29++%7D%7B%282+%2B++%5Csqrt%7B5%7D%29%282+-++%5Csqrt%7B5%7D%29++%7D+%29)
![p + q = ( \frac{ {(2 - \sqrt{5)} }^{2} + {(2 + \sqrt{5)} }^{2} }{ {2}^{2} - { \sqrt{5} }^{2} } ) p + q = ( \frac{ {(2 - \sqrt{5)} }^{2} + {(2 + \sqrt{5)} }^{2} }{ {2}^{2} - { \sqrt{5} }^{2} } )](https://tex.z-dn.net/?f=p+%2B+q+%3D+%28++%5Cfrac%7B+%7B%282+-++%5Csqrt%7B5%29%7D+%7D%5E%7B2%7D+%2B++%7B%282+%2B++%5Csqrt%7B5%29%7D+%7D%5E%7B2%7D++%7D%7B+%7B2%7D%5E%7B2%7D+-++%7B+%5Csqrt%7B5%7D+%7D%5E%7B2%7D++%7D+%29)
![p + q = ( \frac{4 + 5 - 4( \sqrt{5}) + 4 + 5 + 4( \sqrt{5}) }{4 - 5} ) p + q = ( \frac{4 + 5 - 4( \sqrt{5}) + 4 + 5 + 4( \sqrt{5}) }{4 - 5} )](https://tex.z-dn.net/?f=p+%2B+q+%3D+%28+%5Cfrac%7B4+%2B+5+-+4%28+%5Csqrt%7B5%7D%29+%2B+4+%2B+5+%2B+4%28+%5Csqrt%7B5%7D%29++%7D%7B4+-+5%7D+%29)
![p + q = ( \frac{4 + 5 + 4 + 5}{ - 1}) p + q = ( \frac{4 + 5 + 4 + 5}{ - 1})](https://tex.z-dn.net/?f=p+%2B+q+%3D+%28+%5Cfrac%7B4+%2B+5+%2B+4+%2B+5%7D%7B+-+1%7D%29+)
![p + q = - 18 p + q = - 18](https://tex.z-dn.net/?f=p+%2B+q+%3D++-+18)
p=(2-√5)/(2+√5)
And q=(2+√5)/(2-√5)
Then We Find The Value Of p+q
Similar questions
Hindi,
8 months ago
Computer Science,
8 months ago
Geography,
1 year ago
Chemistry,
1 year ago
Math,
1 year ago